Leafhopper tribe Stegelytrini (Hemiptera: Cicadellidae: Deltocephalinae) of the Indian subcontinent, with a note on Aeternus hieroglyphicus Distant (Cicadellidae: Athysanini) - Viraktamath, C. A.; Yeshwanth, H. M.; Webb, M. D. (Zootaxa, 2020)
A checklist of leafhoppers of the tribe Stegelytrini from the Indian subcontinent and a key to genera are given. Two new species, Pachymetopius anamikus sp. nov. (India: Meghalaya) and Yaontogonia unipuncta sp. nov. (India: Arunachal Pradesh) are described and illustrated. Genus Aeternus Distant with its type species A. hieroglyphicus Distant is redescribed based on the male genitalia and its tribal placement is discussed. Habitus images of types of species except Aculescutellaris hirtellus Zhang, Wei & Webb are given.